Elevated secreted frizzled‐related protein 4 in obesity: A potential role in adipose tissue dysfunction. (16th October 2014) - Garufi, Gabriella; Seyhan, Attila A.; Pasarica, Magdalena
<x xml:space="preserve">Abstract</x> Objectives Rarefaction and inflammation of adipose tissue contributes to insulin resistance in obesity. It was hypothesized that angiostatic secreted frizzled‐related protein 4 (SFRP4) causes adipose tissue rarefaction and leads to inflammation and ultimately insulin resistance in obese patients. Methods Abdominal subcutaneous adipose tissue (AbdAT), gluteal subcutaneous adipose tissue (GlutAT), and blood from 15 lean and obese subjects were collected. Circulating‐SFRP4 was measured by ELISA. Body composition was measured by DEXA and insulin sensitivity by the euglycemic hyperinsulinemic clamp. Adipose tissue was analyzed using qRT‐PCR for mRNA gene expression, Luminex system for tissue cytokine release, immunohistochemistry for labeling adipose capillaries, and osmium fixation and Coulter counting for adipocyte sizing. Results Circulating‐SFRP4 was higher in obese vs. lean subjects (137.8 ± 33.6 ng ml−1 vs. 64.1 ± 23.8 ng ml−1, P < 0.05). Circulating‐SFRP4 significantly (P < 0.05) correlated with body fat percentage (R = 0.07), body mass index (R = 0.07), insulin sensitivity (R = −0.66). Circulating‐SFRP4 correlated with AbdAT‐VEGF (R = −0.67, P < 0.05), AbdAT‐capillary density (R = −0.65, P < 0.05), secreted‐MIP1α (R = 0.74), and AbdAT‐SFRP4 mRNA (R = 0.60). AbdAT‐SFRP4 mRNA significantly correlated with AbdAT‐capillary density (R = 0.71, P < 0.05), but not with AbdAT mean adipocyte size. There was no difference between AbdAT‐SFRP4 and GlutAT‐SFRP4 mRNA. Interestingly, GlutAT‐SFRP4 correlated with AbdAT mean adipocyte size (P < 0.05). Conclusions The results suggested that AbdAT is a major contributor for circulating‐SFRP4 and that SFRP4 has an important role in obese adipose tissue pathophysiology.